The relationship between Learning Readiness and UKNI Retaker Graduation Results Online Guidance at Sari Mulia University Banjarmasin - Mambang; Basit, Mohammad; Nisa, Reny Ayu (Journal of Engineering, Technology, and Applied Science (JETAS), 2022)
Masih rendahnya persentasi kelulusan mahasiswa pada uji kompetensi ners pada bulan oktober 2018 khususnya pada 5 isntitusi swasta yang ada di kalimantan selatan yang mengikuti sebanyak 641 peserta dan yang dinyatakan tidak kompeten sebanyak 367 peserta. Permasalah yang sering rateker alami yaitu lokasi tempat tinggal yang tersebar, dari masalah tersebut rateker mengikuti bimbel secara online. Melalui bimbel online ada permasalahan yang dialami yaitu kurang pemahaman dalam menganalisis soal, kurang semangat belajar, kurang fokus mengikuti bimbel, dan kesibukan bekerja pada saat mengikuti bimbingan belajar online. Tujuan penelitian ini adalah untuk mengetahui Hubungan Kesiapan Belajar terhadap Hasil Kelulusan Rataker UKNI Bimbingan online Universitas Sari Mulia Banjarmasin. Penelitian ini menggunakan pendekatan kuantitatif. Pengumpulan data primer dengan kuesioner, diambil dengan teknik total sampling dan data dianalisis mengunkan uji chi Square. Berdasarkan kesiapan belajar yang mempengaruhi hasil kelulusan menyatakan bahwa dari 39 responden yang dinyatakan kesiapan belajar yang terbanyak adalah kesiapan belajar kurang sebanyak 16 responden dengan hasil kekulusan tidak kompeten sehingga dapat disimpulkan bahwa rendahnya kesiapan belajar cukup kuat untuk mempengaruhi dan akan menurukan hasil kelulusan. The relationship between Learning Readiness and UKNI Retaker Graduation Results Online Guidance at Sari Mulia University Banjarmasin Abstract: The percentage of student graduation is still low in nurses' competency test in October 2018 especially in the 5 private institutions in South Kalimantan that participated in as many as 641 participants and 367 participants were declared incompetent. The problem that is often a natural rateker is the location of a scattered residence, from these problems rateker follow tutoring online. Through online tutoring there are problems that are experienced namely lack of understanding in analyzing questions, lack of enthusiasm for learning, lack of focus in taking lessons, and busy working when following online tutoring. Reserach Objective is to find out the Relationship between Learning Readiness and UKNI Rataker Graduation Results Online Tutoring at Sari Mulia University, Banjarmasin. This research uses a quantitative approach. Primary data collection by questionnaire, taken with total sampling techniques and analyzed data using chi square test. Based on the readiness of learning that affects the graduation results stated that of the 39 respondents who stated the most learning readiness was less readiness as many as 16 respondents with incompetent sincerity results. That the lack of learning readiness is strong enough to influence and will reduce the graduation results. Keywords: Graduation Results, Learning Readiness, UKNI.